Retail Philanthropy: Firm Size, Industry, and Business Cycle - Amato, Louis; Amato, Christie H. (2012)
This article investigates the effects of firm size, profitability, industry affiliation, and the business cycle on retailer philanthropy. The importance of industry and firm effects on giving was analyzed with regression models using industry-fixed effects as well as firm strategy variables. The analysis included instrumental variables methodology to account for simultaneity in the charitable giving–profits relationship. Data were gathered from the IRS Corporate Statistics of Income Sourcebook, data that provide firm size class measures covering the entire firm size distribution ranging from small retailers up to large multi-national retail firms. Retailer philanthropy was measured as the ratio of charitable contributions to total receipts. Important findings include a cubic relationship between retailer philanthropy and firm size; industry effects stronger than those observed for retail profit; and the absence of business cycle effects. The empirical research relating retail charitable giving to firm attributes including firm size and advertising, industry and business cycle factors are unique in the business ethics literature. Prior studies regarding the importance of industry on charitable giving utilized data across broad sectors of the economy. Firms from different sectors could be expected to differ in philanthropic approach due to differences in public contact as well as differences in public relations exposure. The strong industry effects reported for this sample of exclusively retail firms, with similar public contact, provide strong evidence for the importance of industry in determining firms’ charitable strategies.
Keywords: Retailing; Philanthropy; Industry; Firm Size